Para una teoría del arte en Historia y estilo, de Jorge Mañach - Arencibia Coloma, Yaneidys (Raleigh, NC : Editorial A Contracorriente, 2018)
For a theory of art in History and style exposes the contribution of Jorge Manach (1898-1961) to the theory of Cuban art, through the examination of History and style (1944), containing several fundamental texts, and through the use of concepts of analysis as "electivism, "long duration" and "theory of the historical circumstantiality of style", by virtue of specifying the method used by Manach, the historiographical conception that supports his proposal and the use of the essay as a textual support.
Cover; Half Title; Title; Copyright; Dedication; Contenido; Agradecimientos; Introducción; CAPÍTULO I: Fundamentos teóricos y metodológicos presentes en Historia y estilo; CAPÍTULO II: Historia y estilo. Importancia para la teoría del arte en Cuba; Epílogo; Notas; Bibliografía; Back Cover
Online resource; title from PDF title page (EBSCO, viewed May 17, 2018).
Includes bibliographical references.
JSTOR
Keywords: Mañach, Jorge, -- 1898-1961.; Mañach, Jorge, -- 1898-1961; Art, Cuban; Art cubain; ART -- Sculpture & Installation; Art, Cuban